PELATIHAN DAN PENDAMPINGAN PEMBUATAN SABUN CUCI PIRING ALAMI DARI DAUN PANDAN DAN JERUK NIPIS DI BANJAR BATAN POH DESA SANUR KAJA - A.A. Istri Mirah Dharmadewi; Ni Ketut Erawati; Ni Luh Gede Widhi Adnyani; Lalu Muhamad Gilang; Ika Andani; Maulira Yunika; Luluk Fauziah; Kartika Lusiana; Raihan Fadhillah (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This community service activity aims to empower housewives' groups in Banjar Batan Poh, Sanur Kaja, through training in making dish soap made from natural ingredients as an environmentally friendly, safe, and economical alternative. The soap is made from pandanus and lime leaves which are easily available and contain antiseptic and antibacterial compounds. The method used was a participatory approach that included five stages: preparation, socialization, training on making, packaging, and evaluation. The results of the activity showed a significant increase in participants' understanding and skills; 92% understood the importance of environmentally friendly products, 88% were able to recreate them independently, and 80% were interested in making them a business opportunity. This activity not only provides environmental education, but also opens up business opportunities based on local potential and strengthens collaboration between universities and communities in creating sustainable development.